1993
DOI: 10.1029/93rs00359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the acoustic and radar pulse length ratio on the accuracy of radio acoustic sounding system (RASS) temperature measurements with monochromatic acoustic pulses

Abstract: This paper is concerned with the accuracy of temperature measurements with radio acoustic sounding system (RASS) consisting of a pulsed Doppler radar and an acoustic source, where the latter excites short monochromatic pulses. Through the use of a numerical model and middle and upper atmosphere (MU) radar experiments, we found that the accuracy is significantly affected by the acoustic and radar pulse length ratio. When the Bragg condition is not strictly satisfied, a numerical model predicted that the mean fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Increased maximum altitudes can be achieved by using multiple acoustic sources placed at various points around the radar, or by employing fast and flexible beam-steering. For example, Adachi et al (1993) demonstrated excellent agreement with radiosondes up to an altitude of 10 km when using the MU radar in fast beam-steering mode. Other useful work related to RASS includes publications by Peters et al (1985), May et al (1988May et al ( , 1990May et al ( , 1996, Angevine et al (1994), Tsuda et al (1994), and Yamamoto et al (1996).…”
Section: Tropospheric Temperature Measurementsmentioning
confidence: 93%
“…Increased maximum altitudes can be achieved by using multiple acoustic sources placed at various points around the radar, or by employing fast and flexible beam-steering. For example, Adachi et al (1993) demonstrated excellent agreement with radiosondes up to an altitude of 10 km when using the MU radar in fast beam-steering mode. Other useful work related to RASS includes publications by Peters et al (1985), May et al (1988May et al ( , 1990May et al ( , 1996, Angevine et al (1994), Tsuda et al (1994), and Yamamoto et al (1996).…”
Section: Tropospheric Temperature Measurementsmentioning
confidence: 93%
“…This is the first active phased-array 1.3-GHz band wind profiler radar. It also enables observations of atmospheric temperature using the radio acoustic sounding system (RASS) technique with speaker horns (e.g., Adachi et al 1993;May et al 1996). The same radar system is adopted in the wind profiler network, the Wind Profiler Data Acquisition System (WINDAS), of the Japan Meteorological Agency (JMA) (Ishihara and Goda 2000;Kato et al 2004).…”
Section: Rasc (Radio Science Center For Space Andmentioning
confidence: 99%
“…Since we required the acoustic signal to include frequency components satisfying the Bragg condition in the measurement height range, we decided to sweep the frequency within the pulse length (e.g., Adachi et al 1993;Masuda et al 1992). It is expected that the maximum and minimum temperatures observed with LTR/RASS in Japan are about 30 C (which is the temperature near the ground in summer) and about À20 C (which is the temperature at the top of the ABL in winter), respectively.…”
Section: System Requirementsmentioning
confidence: 99%
“…The Radio Acoustic Sounding System (RASS) capabilities to measure virtual temperature profiles using a wind profiler have already been widely attested (Adachi et al, 1993;Angevine et al, 1994;May et al, 1989;Peters, 2000;Klaus et al 1998). This technology, involving acoustic transmission in the atmosphere combined with an UHF or a VHF radar, is potentially one of the most promising tools for an automated continuous temperature profiling due to its accuCorrespondence to: V. Klaus (vladislav.klaus@meteo.fr) racy and efficiency in all weather conditions.…”
Section: Introductionmentioning
confidence: 99%